Correlation between Prolactin Serum with Neutrophil Lymphocyte Ratio (NLR) in Systemic Inflammatory Response Syndrome - Dwi Retnoningrum; Meita Hendrianingtyas; Hermawan Istiadi; Ardhea Jaludamascena (Diponegoro International Medical Journal, 2021)
Background: Systemic inflammatory response syndrome (SIRS) is a state of systemic inflammatory activation by various causes. SIRS have a high mortality rate. Prolactin is known to regulate cellular function of immune system.  Neutrophil-lymphocyte ratio (NLR) is simple, cost effective and easy parameter that currently used as inflammation marker.Objective: The aims of this study is to determine the correlation between prolactin serum with NLR in SIRS patients.Methods: A cross sectional study was conducted on 50 clinically SIRS patients. Prolactin serum was measured by enzyme linked immunosorbent assay (ELISA) and NLR was calculated manually from absolute neutrophil and lymphocyte count measured by automatic hematology analyzer. Non-parametric Spearman test was used to analyze the correlation between prolactin with NLR.Results: Median value of serum prolactin level was 11.32 ng/mL (2.76-194.81), whereas the mean value NLR was 16.36 ± 11.58. The correlation between prolactin levels with NLR was r = 0.345, p = 0.014.Conclusion: There is a weak positive significant correlation between prolactin with neutrophil lymphocyte ratio in SIRS